MANAJEMEN PENGELOLAAN DAN PEMBERDAYAAN TANAH WAKAF DI KECAMATAN KEMUNING KOTA PALEMBANG - Alfarisi, Muhammad Salman; Kumala, Destiana (I-Economics, 2021)
Waqf is an Islamic religious teaching that aims to build prosperity and develop an advanced civilization. The type of research used by researchers in this study is qualitative research, namely field research conducted by interview, observation, and describing facts in the field. The results of this study indicate that waqf land in Kemuning District, Palembang City is used for the establishment of a tahfidz foundation and mosque construction, as well as for school operations. According to a review of Islamic law in the management of waqf land in Kemuning District, Palembang City, it does not conflict with Islamic law. This can be seen from the business carried out that there is nothing that is contrary to Islamic law and in its implementation there are no elements that are forbidden. In the future, it is necessary to provide education about waqf, especially productive waqf, to nadzir in Kemuning Subdistrict, Palembang City so that its management is more optimal in developing waqf assets productively. Ministry of Religion agencies must actively provide counseling and coordinate with the Land Office, Nadzir, and PPAIW so that their roles and functions can run optimally so that they can increase productive waqf land in Kemuning District, Palembang City.